TANGGUNG JAWAB MAHASISWA JURUSAN PMIPA UNIVERSITAS LAMBUNG MANGKURAT DALAM PEMBELAJARAN FISIKA - Suyidno Suyidno; Mohamad Nur; Leny Yuanita; Titin Sunarti; Binar Prahani (FKIP ULM, 2016)
Abstract. Responsibility as life skills and career 21st century. There is still limited knowledge and have not been integrated in a comprehensive manner. The goal of this study is to identify student’s responsibility Department PMIPA of Lambung Mangkurat University in learning Physics. This study used a qualitative approach with survey method. Subjects were 156 students of biology education; chemistry education, physical education, and science education are a program fundamental physics course. Data collected from questionnaires, observations, and interviews. Data were analized by descriptive qualitative and quantitative. The results of questionnaire showed that most students feel responsible for participating, respect for others, teamwork, leadership, and expression with the criteria of good/excellent, but the observations and interviews show that a lot of student are difficulties in leading and expression, as well as some students still deficient/sufficient in participating, respect for others, and team work. Keywords: Responsibility, Fundamental Physics Abstrak. Tanggung jawab sebagai keterampilan hidup dan berkarir abad 21 ternyata masih diajarkan sebatas pengetahuan dan belum diintegrasikan secara komprehensif. Tujuan penelitian ini adalah mengidentifikasi tanggung jawab mahasiswa Jurusan PMIPA Universitas Lambung Mangkurat dalam pembelajaran fisika. Penelitian ini menggunakan pendekatan kualitatif dengan metode survey. Subyek penelitian adalah 156 mahasiswa pendidikan biologi, pendidikan kimia, pendidikan fisika, dan pendidikan sains yang memprogram mata kuliah fisika dasar. Pengumpulan data menggunakan angket, pengamatan, dan wawancara. Teknik analisis data secara deskriptif kualitatif dan kuantitatif. Hasil angket menunjukkan bahwa sebagian besar mahasiswa merasa bertanggung jawab dalam berpartisipasi, menghormati orang lain, kerja sama, memimpin, dan menyampaikan pendapat dengan kriteria baik/sangat baik, tetapi hasil pengamatan maupun wawancara menunjukkan bahwa sebagian besar mahasiswa kesulitan dalam memimpin dan menyampaikan pendapat, serta beberapa mahasiswa masih kurang/cukup dalam berpartisipasi, menghormati orang lain, dan kerja sama. Kata kunci: Tanggung Jawab, Fisika Dasar